About the buried soils of the Ferghana region - (Uchkoprik district on the example of the Sarikurgan hill) (Texas Journal of Agriculture and Biological Sciences, 2025)
The main occurrence of buried soils on the Sarigurgan hill, which is now located in the Ferghana region, is to study their properties and composition. It was also studied how the fortress, which served as a fortress in ancient times, appeared over the centuries, and its functions.